2013
DOI: 10.1002/2013jd020203
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of mesopause zonal winds over Ascension Island: Coupling to the stratospheric QBO

Abstract: [1] Zonal-wind measurements obtained between October 2001 and July 2011 with the SKiYMET meteor radar located at Ascension Island (8 ı S, 14 ı W) have been used to study the interannual variability at meteor ablation altitudes (approximately 78-100 km) and its coupling to the stratospheric quasi-biennial oscillation (QBO). An upper mesospheric QBO (MQBO) with a period of 27.5 months has been detected throughout the observational period. The MQBO is found to be out-of-phase with the stratospheric QBO (SQBO) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
7
20
0
Order By: Relevance
“…Usually the QBO winds are asymmetric with a strong westward wind phase (as strong as about −40 m s −1 ) and much weaker eastward winds (only about 20 m s −1 at maximum). The SAO has a period of 6 months, and both eastward and westward winds can be quite strong: about −60 to −20 m s −1 for westward wind, and about 20 to 40 m s −1 for eastward wind (e.g., Hirota, 1980;Delisi and Dunkerton, 1988;Dee et al, 2011, and references therein). More details about QBO and SAO can be found in Baldwin et al (2001) and references therein.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually the QBO winds are asymmetric with a strong westward wind phase (as strong as about −40 m s −1 ) and much weaker eastward winds (only about 20 m s −1 at maximum). The SAO has a period of 6 months, and both eastward and westward winds can be quite strong: about −60 to −20 m s −1 for westward wind, and about 20 to 40 m s −1 for eastward wind (e.g., Hirota, 1980;Delisi and Dunkerton, 1988;Dee et al, 2011, and references therein). More details about QBO and SAO can be found in Baldwin et al (2001) and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…This filtering of waves is relevant for the formation of circulation patterns at higher altitudes. For example, the pre-filtered wave spectrum is likely responsible for the formation of a QBO and an SAO in the tropical mesopause region (see also Dunkerton, 1982;Burrage et al, 1996;Baldwin et al, 2001;Richter and Garcia, 2006;Peña-Ortiz et al, 2010;de Wit et al, 2013;Kishore Kumar et al, 2014, and references therein). It has also been found that the QBO and the SAO interact with each other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9a of PO10. It is also interesting to note that de Wit et al (2013) found similar structures in correlations between the mesospheric and stratospheric monthly-mean winds. In particular, they found a positive correlation of the 90 km wind with the 70 hPa wind, while the correlation was negative for 20 hPa.…”
Section: Resultsmentioning
confidence: 54%
“…In addition, they modulate the semi-annual oscillation (SAO) in the stratopause region and contribute to the wind variations in the mesosphere (Andrews et al 1987;Baldwin et al 2001;Plumb 2002;Fritts and Alexander 2003;Haynes 2005;Shepherd 2007). Observations of inter-annual (year-to-year) variations of winds in the equatorial upper mesosphere (80-100 km) are available for the last decades (Garcia et al 1997;Day and Mitchell 2013;de Wit et al 2013;Kishore Kumar et al 2014). Strong easterly wind anomalies during early spring (so-called Mesospheric Spring Equinox Enhancements, MSEE) are usually observed during the westerly phase of the QBO (hereafter: QBO-West) (Garcia et al 1997), but not in all years.…”
Section: Introductionmentioning
confidence: 99%